2011
DOI: 10.1007/s10068-011-0105-7
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and evaluation of heat-shock condition for spore enumeration being used in thermal-process verification: Differential responses of spores and vegetative cells of Clostridium sporogenes to heat shock

Abstract: To evaluate a heat-shock condition for the enumeration of Clostridium sporogenes spores, a surrogate for C. botulinum spores, we examined the heat tolerance of C. sporogenes spores and vegetative cells exposed to a heat shock at 90

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 23 publications
(15 reference statements)
0
10
0
Order By: Relevance
“…The activation of dormant spores by heat shock is a process that progresses with time and involves an abrupt change in individual spores rather than a gradual change in all spores, as indicated by increased colony counts with time on conventional plating media (41). On the other hand, if heat-shock treatment is too severe, the damage will be so strong that the spores cannot repair themselves and the viable spore counts will be smaller, compared with the conventional and mild heat-shock conditions (27). Our results revealed that heat shock of 68°C for 20 min was above the critical minimum heat activation temperature/time combinations for the spores examined (Fig.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The activation of dormant spores by heat shock is a process that progresses with time and involves an abrupt change in individual spores rather than a gradual change in all spores, as indicated by increased colony counts with time on conventional plating media (41). On the other hand, if heat-shock treatment is too severe, the damage will be so strong that the spores cannot repair themselves and the viable spore counts will be smaller, compared with the conventional and mild heat-shock conditions (27). Our results revealed that heat shock of 68°C for 20 min was above the critical minimum heat activation temperature/time combinations for the spores examined (Fig.…”
Section: Discussionmentioning
confidence: 61%
“…Dormancy phase may be broken by heat treatment at a time and sublethal temperature appropriate to the organism concerned (24,25). Further, there has been a revival of interest in validating and improving the procedure for enumeration of Bacillus spores by using different heat shock (or heat-activation) treatments (23,26,27). The heat shock step as an effective germinant has usually two functions: 1) activate the spores and so start or enhance of germination for all spores; 2) killing or destructing all kinds of vegetative cells in the sample, thereby to provide reliable counts of spores with no viability loss (24,28,29).…”
mentioning
confidence: 99%
“…Notably, while the average values of times for fast release of CaDPA (Δ T release ) in the L -alanine germination of multiple individual spores were similar with spores with and without a heat shock, optimally heat-shocked spores showed the lowest values of T 1 , T lag1 , T release , and T lys , ( Table 1 ). These results suggest that the primary effect of an optimal heat shock on C. sporogenes spore germination is to shorten the T 1 values for individual spores, as seen with spores of other species ( Yi and Setlow, 2010 ; Zhang et al, 2010a ; Byun et al, 2011 ; Setlow et al, 2017 ).…”
Section: Resultsmentioning
confidence: 78%
“…As expected, the thermal treatment (70 °C for 10 min) determined a reduction in absorbance (approximately 15%), as it is well known that a slight heat shock can activate spores (Byun et al ., ). A promoting effect on spore germination was also achieved by l ‐alanine (absorbance was reduced by 25%), but this was an expected result as it is well known that l ‐alanine induces spore germination (Barlass et al ., ).…”
Section: Resultsmentioning
confidence: 99%